Illegal Online Lending in Indonesia: Mapping Criminal Liability and Strengthening Victim Protection - Zulfiani, Anita; Nabila Alinka Wiboo; Satyalalita, Skolastika Pradnya (JUSTISI, 2026)
This study aims to analyze the forms of criminal liability of illegal online loan providers and to formulate a legal protection model for victims within the framework of national criminal law. The method used is normative juridical with a legislative and conceptual approach, through an examination of various related regulations, court decisions, and criminal law and consumer protection doctrines. The novelty of this research lies in its comprehensive mapping of the criminal liability regime for illegal online lending across laws-including the Criminal Code, the Electronic Information and Transactions Law, the Personal Data Protection Law, the Consumer Protection Law, the Trade Law, OJK regulations, and the Money Laundering Law-as well as its affirmation of the function of criminal punishment as a preventive legal protection instrument for potential victims. The results of the study show that illegal online lending practices fulfill the elements of various criminal acts, including fraud, extortion, defamation, threats, dissemination of false information, misuse of personal data, misleading promotion, unlicensed business activities, and money laundering, so that the perpetrators can be held cumulatively criminally liable. In addition, criminal law enforcement against perpetrators serves as a form of preventive and repressive protection for the community. The conclusion of this study confirms that strengthening integrated criminal law enforcement that is victim-oriented and supported by public legal and financial literacy is a key prerequisite for suppressing illegal online lending practices and protecting the public from the trap of technology-based financial crime.